Upaya Peningkatan Prestasi Belajar IPS Siswa Kelas VII SMP Negeri 3 Ngawi Melalui Pendekatan Learning Community Tahun 2024/2025: Penelitian - Penty Puspitasari; Ninik Srijani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to improve student learning achievement in Social Sciences (IPS) subjects through the application of the learning community approach to class VII students of SMP Negeri 3 Ngawi in the 2024/2025 academic year. This study is a Classroom Action Research (CAR) which is carried out in two cycles, each consisting of the stages of planning, action implementation, observation, and reflection. Data were obtained through questionnaires, observations, interviews, and learning outcome tests. The results of the study showed a significant increase in learning achievement. In the pre-cycle stage, the average student score was 63.33 with a completion rate of 50%. After the application of the learning community approach, in cycle I the average score increased to 69.89 with a completion rate of 65%, and in cycle II it increased to 83.3 with a completion rate reaching 90%. These results indicate that the learning community approach is effective in improving students' social studies learning achievement. Therefore, this learning model is recommended to be applied in social studies learning in junior high schools